1979
DOI: 10.1007/bf00267544
|View full text |Cite
|
Sign up to set email alerts
|

The control region of the F sex factor DNA transfer cistrons: Physical mapping by deletion analysis

Abstract: A technique has been developed which allows the isolation of random deletions extending from unique restriction enzyme sites in plasmid DNA molecules. The method involves transformation of E. coli cells with linear plasmid DNAs generated by restriction enzyme cleavage. We have used this technique to map DNA transfer genes in the tra control region of F sex factor DNA. Deletions within EcoRI fragment f6 of F DNA have been isolated and used to assign physical locations to tra genes by a combination of genetic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
1

Year Published

1981
1981
1994
1994

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 27 publications
2
11
1
Order By: Relevance
“…Low transfer levels were also reported and similarly interpreted by Miki et al (17). (1,25,26). We also found that while pBE269 exhibited low complementing activity for transfer of F lac traB2 (Table 3), the pBE269/F lac traB strain remained resistant to male specific phages.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Low transfer levels were also reported and similarly interpreted by Miki et al (17). (1,25,26). We also found that while pBE269 exhibited low complementing activity for transfer of F lac traB2 (Table 3), the pBE269/F lac traB strain remained resistant to male specific phages.…”
Section: Resultssupporting
confidence: 89%
“…1. Our fragment sizes were consistent with reports from other laboratories (1,12,13,23,25,26,29,31). However, consideration of available DNA sequence data and the double-digestion patterns of cloned fragments led us to alter the relative positions of some sites depicted on these earlier maps.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In previous analyses of tra products, only one polypeptide of approximately 24,000 Da has been identified, and it was weakly expressed in all cases (1,14,29); no precursor polypeptide was detected. Resolution of tra proteins in this size range is difficult because of the large number of tra proteins close to the 25,000-Da range; this may explain the inability to detect a precursor product.…”
Section: Discussionmentioning
confidence: 89%
“…Attempts to overexpress the TraK protein from the traK-containing fragment of pOSKI placed under the control of an inducible T7 RNA polymerase promoter were unsuccessful. This suggests that TraK expression may be influenced by the presence of one or more tra genes within the larger fragments used previously (1,14,29) to detect the traK gene product.…”
Section: Discussionmentioning
confidence: 97%